2018
DOI: 10.1177/0269216318772267
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spiritual care on quality of life and spiritual well-being among patients with terminal illness: A systematic review

Abstract: It is suggested that healthcare professionals integrate spiritual care with usual care in palliative care. When providing spiritual care, healthcare professionals should take into consideration patients' spiritual needs, preference, and cultural background. More multicenter and disciplinary studies with rigorous designs are needed in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 51 publications
2
64
0
9
Order By: Relevance
“…There is a growing incidence of cancer worldwide [6], and meeting the spiritual needs of patients is a vital aspect of care [1]. Patients with serious illness and end-oflife issues have the desire to include spirituality in their care [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing incidence of cancer worldwide [6], and meeting the spiritual needs of patients is a vital aspect of care [1]. Patients with serious illness and end-oflife issues have the desire to include spirituality in their care [18].…”
Section: Discussionmentioning
confidence: 99%
“…This research received no specific grant from any funding agency in the public, commercial, or not-for-profit sectors. 1 Psycho-Oncology Unit, Azienda USL-IRCCS di Reggio Emilia, Reggio Emilia, Italy. 2 SC Infrastruttura Ricerca e Statistica, Azienda USL-IRCCS di Reggio Emilia, Reggio Emilia, Italy.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Research has shown that the enhancement of nurses' spiritual health not only boosts their personal satisfaction with life [12,13] but also reduces job burnout [14] and assists them with providing spiritual care to patients in their clinical work. Nurses are the chief providers of spiritual care to patients [15][16][17], and a close relationship exists between nurses' attitude and ability to provide spiritual care to patients and their perceptions of spirituality and spiritual health [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Spiritual care encompasses an attitude and behaviour shaped by nurses' spiritual nursing values [22,23] (especially the affirmation of attributes such as human dignity, goodness, benevolence, peace of mind, warmth, self-care, and care for others) and consists of care that reflects individuals' cultures and beliefs provided after assessing their spiritual needs and challenges [24]. Spiritual care also consists of nursing methods or activities that rely on the provision of company or care, listening, or religious activities that correspond to patients' beliefs to help them to achieve better physical, mental, social, and spiritual health and comfort [17,25] The purpose of spiritual care is to ease patients' difficulties at the spiritual level and help them find the meaning of life, self-actualization, hope, creativity, faith, trust, peace, comfort, prayer, and the ability to love and forgive in the midst of suffering and disease [17,26]. Additionally, spiritual care seeks to help patients to face their fears of death, mitigate the uncertainty and discomfort of the treatment process, and regain their inner peace [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed that spiritual care including dignity therapy had a potentially beneficial effect on the quality of life and spiritual well-being of patients with terminal illness, suggesting that healthcare professionals should pay greater attention to patients' spiritual well-being (Chen, Lin, Yan, Wu, & Hu, 2018).…”
mentioning
confidence: 99%